Over-the-scope clips vs standard endoscopic interventions for first-line treatment of NVUGI bleeding: Meta-analysis of randomized trials - Mega, Paulo Ferreira; Brunaldi, Vitor Ottoboni; Bestetti, Alexandre Moraes; Kum, Angelo So Taa; de Sousa, Igor Valdeir; Lera dos Santos, Marcos Eduardo; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2025)
Background and study aims Recently, over-the-scope clips (OTSCs) have been extensively studied for hemostasis of nonvariceal upper gastrointestinal bleeding (NVUGIB). Our goal was to compare the efficacy of OTSCs with standard endoscopic interventions (SEIs) as first-line treatments.Patients and methods A comprehensive search of electronic databases was performed to identify randomized clinical trials (RCTs) comparing OTSCs with SEIs as first-line therapy for NVUGIB. This search was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines.Results Of 819 reviewed studies, five RCTs comprising 555 patients (277 OTSCs vs. 278 SEIs) were included. The OTSC group had a lower 30-day rebleeding rate (risk ratio [RR] 0.43; 95% confidence interval [CI] 0.24–0.77; I² = 0%; P = 0.004) and a higher clinical success rate (RR 1.19; 95% CI 1.11–1.28; I² = 0%; P < 0.00001). There was no significant difference in technical success (RR 1.06; 95% CI 0.98–1.14; I² = 73%; P = 0.13), 30-day all-cause mortality (RR 0.50; 95% CI 0.22–1.14; I² = 0%; P = 0.10), need for further intervention (RR 1.22; 95% CI 0.43–3.47; I² = 0%; P = 0.71), or length of hospital stay (mean difference 0.31; 95% CI: -1.08- 1.70; I² = 0%; P = 0.66). Risk of bias, which was assessed using the Cochrane Risk of Bias 2.0 tool, indicated some concerns about bias.Conclusions OTSCs are more efficient than SEIs as first-line treatment in terms of rebleeding within 30 days and clinical success rates.
Keywords: Endoscopy Upper GI Tract; Non-variceal bleeding; Ulcers (peptic and other); Dilation, injection, stenting